Grey Literature in Library and Information Studies - Dominic Farace; Joachim Schöpfel (De Gruyter Saur, 2010)
The further rise of electronic publishing has come to change the scale and diversity of grey literature facing librarians and other information practitioners. This compiled work brings together research and authorship over the past decade dealing with both the supply and demand sides of grey literature. While this book is written with students and instructors of Colleges and Schools of Library and Information Science in mind, it likewise serves as a reader for information professionals working in any and all like knowledge-based communities.